"Multiculturality" as a key methodological challenge during in-depth interviewing in international business research. Issue 2 (29th April 2016) - Zhang, Ling Eleanor; Guttormsen, David S. A.
Abstract : Purpose: – Although qualitative methods have now gained a stronger foothold in international business (IB) research, they remain under researched, especially regarding how researchers can overcome obstacles created when interviewers exhibit "multiculturality" during international field research projects. The purpose of this paper is to analyse how researchers' multicultural backgrounds create challenges and opportunities in data collection during in-depth interviewing, and how such backgrounds further impact on the power imbalance between researchers and interviewees. Design/methodology/approach: – The two multicultural co-authors of this paper draw upon their 141 in-depth interview experiences with expatriates and local staff across five separate field research projects in Mainland China, Hong Kong SAR, South Korea, Finland, and the USA. Field research experiences are analysed through a Bourdieusian-inspired "epistemic reflexive" self-interrogation process between the two co-authors. Findings: – This paper suggests five strategies to cope with the power imbalance between the researcher and the respondent in terms of social categorisation and language: activating the "favoured" ethnicity, putting the "desired" passport forward, constantly reassuring of belonging to the "right" social category, bonding in the interviewee's mother tongue, and adopting a multilingual approach characterised by frequent code-switching. Originality/value: – This paper emphasises the relevance of exploratory, self-reflexive analysis, and uncovers how social categorisation and language influence the interviewer-interviewee power imbalance. Distinct methodological contributions are proposed accordingly for IB literature: placing "multiculturality" as an important concept at the forefront of qualitative IB research; and identifying ethnicity and accent as key factors in terms of securing and conducting interviews.